Plasticity in the Oxidative Folding Pathway of the High Affinity Nerita Versicolor Carboxypeptidase Inhibitor (NvCI) - Esperante, Sebastian (2017)
Nerita Versicolor carboxypeptidase inhibitor (NvCI) is the strongest inhibitor reported so far for the M14A subfamily of carboxypeptidases. It comprises 53 residues and a protein fold composed of a two-stranded antiparallel β sheet connected by three loops and stabilized by three disulfide bridges. Here we report the oxidative folding and reductive unfolding pathways of NvCI. Much debate has gone on whether protein conformational folding guides disulfide bond formation or instead they are disulfide bonds that favour the arrangement of local or global structural elements. We show here that for NvCI both possibilities apply. Under physiological conditions, this protein folds trough a funnelled pathway involving a network of kinetically connected native-like intermediates, all sharing the disulfide bond connecting the two β-strands. In contrast, under denaturing conditions, the folding of NvCI is under thermodynamic control and follows a "trial and error" mechanism, in which an initial quasi-stochastic population of intermediates rearrange their disulfide bonds to attain the stable native topology. Despite their striking mechanistic differences, the efficiency of both folding routes is similar. The present study illustrates thus a surprising plasticity in the folding of this extremely stable small disulfide-rich inhibitor and provides the basis for its redesign for biomedical applications.